Surface coated cutting tools

By applying a hard coating layer with specific residual stress distribution on the substrate of surface-coated cutting tools, both wear and defect resistance are significantly improved, addressing the limitations of existing tools in long-term performance and high-toughness material cutting.

JP7649468B2Active Publication Date: 2025-03-21MITSUBISHI MATERIALS CORP
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
JP2021038509
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-10
Publication Date
2025-03-21
Estimated Expiration
2041-03-10

AI Technical Summary

Technical Problem

Existing surface-coated cutting tools face challenges in achieving both excellent wear resistance and defect resistance, especially during long-term use and in applications involving high toughness materials like stainless steel.

Method used

The surface-coated cutting tool features a hard coating layer with a lower Ti nitride or carbonitride layer and an upper Al and Ti composite nitride or carbonitride layer, applied using chemical vapor deposition. The tool substrate undergoes pretreatment or post-treatment with wet blasting or dry crust to intentionally apply residual stress, ensuring a compressive residual stress on the flank surface and a higher stress on the rake surface, with a significant difference between the two.

Benefits of technology

This approach enhances the tool's wear resistance and fracture resistance, preventing early wear damage and extending tool life, even under demanding conditions such as intermittent cutting of difficult-to-cut materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007649468000010
    Figure 0007649468000010
  • Figure 0007649468000011
    Figure 0007649468000011
  • Figure 0007649468000001
    Figure 0007649468000001
Patent Text Reader

Abstract

To provide a surface-coated machining tool which is excellent in wear resistance, exerts high defect resistance and is suitable for milling in particular.SOLUTION: The surface-coated machining tool is provided which comprises, on a surface of a tool substrate made of tungsten carbide- based cemented carbide alloy, a lower layer having an average layer thickness of 0.6-21.0 μm and made of Ti nitride or carbonitride and an upper layer having an average layer thickness of 0.5-20.0 μm and including a complex nitride layer made of Ai and Ti having a Nacl type face-centered cubic crystal structure or a complex carbonitride layer, wherein when residual stress of the tungsten carbide-based cemented carbide alloy on a flank face of a cutting blade of the tool substrate is defined as S1 and residual stress of the tool substrate on a rake face of the cutting blade is defined as S2: α)S1<S2, β)S1≤-200 MPa, γ)an absolute value of a difference between S1 and S2 is larger than 250.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a surface-coated cutting tool (hereinafter sometimes simply referred to as a "coated tool") that exhibits excellent cutting performance not only in continuous high-speed cutting but also in intermittent cutting by virtue of the fact that its hard coating layer has excellent chipping resistance and wear resistance. [Background technology]

[0002] In cutting stainless steel or steel materials with remaining cut surfaces, cutting tools coated with AlTiN by the CVD method are known to exhibit high wear resistance in continuous high-speed cutting due to the hardness and oxidation resistance of the coating. On the other hand, in unstable machining such as machining of stainless steel, which has high toughness as a work material, or machining of a welded surface where the depth of cut varies, or in rough machining where a high depth of cut is required with an emphasis on machining efficiency, the high hardness of the coating causes significant particle fall-off, leading to the progression of abnormal damage including tool breakage, and the inherent performance of the tool cannot be demonstrated.

[0003] In contrast, for example, Patent Document 1 describes a hard coating layer formed on a substrate surface by chemical vapor deposition that is made of a composite nitride layer of Ti and Al (TiAlN) or a composite carbonitride (TiAlCN), has a face-centered cubic structure of at least 90 volume %, has a maximum orientation index TC(111) in the (111) plane when subjected to X-ray diffraction and is at least 1.5, and has a residual stress value of 0 MPa or less and -5000 MPa or more in a residual compression state, whereby improved crack resistance and wear resistance as a tool are observed. In addition, the orientation index TC(111) of the (111) plane was derived using the measured X-ray diffraction peak intensities for each of the (111), (200), (220), and (311) crystal planes of the Ti and Al complex carbonitride.

[0004] In Patent Document 2, in a surface-coated cutting tool having a rake face and a flank face, and the boundary portion between them forming a cutting edge, in the (111) plane of a TiAlN layer having a NaCl-type crystal structure with a specific composition formed on the surface of a substrate by CVD method, when the orientation index TC(111) shows a maximum value and 1.0 < TC(111) ≦ 4.0 is satisfied, it is described that a surface-coated cutting tool exhibiting excellent wear resistance and chipping resistance can be obtained. In deriving the orientation index TC(111) of the (111) plane, the measured values of the X-ray diffraction peak intensities for the crystal planes of (111), (200), (220), (311) and (222), which are the crystal growth preferential orientations of the Ti, Al composite carbonitride, are used.

Prior Art Documents

Patent Documents

[0005]

Patent Document 1

Patent Document 2

Summary of the Invention

Problems to be Solved by the Invention

[0006] In recent years, the requirements for labor saving and energy saving in cutting processes have been strong. Along with this, cutting processes tend to be faster and more efficient. In coated tools, due to the occurrence of particle detachment, abnormal damage accompanied by tool chipping occurs, so excellent chipping resistance is required. Furthermore, for long-term use, excellent wear resistance is required. In Patent Document 1 and Patent Document 2, in a coated tool, by orienting the crystal plane of the crystal grains of the Al, Ti composite carbonitride having a cubic crystal structure formed as a hard coating layer by chemical vapor deposition method to the (111) plane, a coated tool having both excellent chipping resistance and wear resistance has been proposed. However, simply orienting the crystal planes of the crystal grains of an Al, Ti composite carbonitride having a NaCl-type crystal structure of a specific composition to the (111) plane and specifying the orientation index within a specific range improves fracture resistance but reduces wear resistance. This means that it is not possible to achieve both fracture resistance and wear resistance, and as a result, there is a problem in that long-term use cannot be realized.

[0007] SUMMARY OF THE PRESENT EMBODIMENTS The present invention has an object to solve the above problems and to provide a surface-coated cutting tool which has excellent wear resistance and high chipping resistance without early wear damage even when used for a long period of time. [Means for solving the problem]

[0008] From the above viewpoints, the present inventors have conducted intensive research in order to achieve an improvement in both fracture resistance and wear resistance of a coated tool having a hard coating layer made of an Al-Ti composite carbonitride formed by chemical vapor deposition, and as a result, have obtained the following findings.

[0009] That is, the inventors have discovered that, when forming a lower layer of a hard coating layer made of CVD-AlTiN on a tungsten carbide-based cemented carbide substrate, for example, by performing a pretreatment such as wet blasting or dry blasting on the cutting edge flank of the substrate, or by performing wet blasting or dry blasting as a post-treatment after the formation of the hard coating layer, or by performing both, it is possible to intentionally impart appropriate values ​​of residual stress to each of the cutting edge flank and rake face of the substrate, thereby obtaining a surface-coated cutting tool with excellent chipping resistance without reducing wear resistance.

[0010] Specifically, the residual stress S1 on the flank face of the cutting edge of the tungsten carbide-based cemented carbide substrate of the surface-coated tool is made smaller than the residual stress S2 on the rake face of the cutting edge (S1 < S2), and a residual stress of at least -200 MPa or less (S1 ≤ -200 MPa), that is, a residual compressive stress of 200 MPa or more is imparted. At the same time, the residual stress S2 on the rake face of the substrate is made larger than the residual stress S1 on the flank face of the cutting edge (S1 < S2), and the absolute value of the difference between S1 and S2 is 250 MPa or more. More preferably, the residual stress S1 on the flank face of the cutting edge is imparted with a residual stress of -850 MPa or less (S1 ≤ -850 MPa), that is, a residual compressive stress of 850 MPa or more. At the same time, the residual stress S2 on the rake face of the substrate is made larger than the residual stress S1 (S1 < S2), and the absolute value of the difference between S1 and S2 is 500 MPa or more. As a result, it has been found that a surface-coated cutting tool excellent in chipping resistance can be obtained without reducing the wear resistance, and is particularly suitable for milling. Here, when the residual stress S1 on the flank face of the cutting edge is, for example, "-200 MPa", it means that the residual stress S1 is a residual compressive stress and the residual compressive stress value is 200 MPa. Also, "S1 ≤ -200 MPa" means that "the residual stress S1 is -200 MPa or less", that is, "the residual compressive stress S1 is 200 MPa or more". The same applies to the residual stress S2 on the rake face of the cutting edge.

[0011] The present invention has been made based on the above findings, "(1) In a surface-coated cutting tool having a hard coating layer on the surface of a tool substrate made of tungsten carbide-based cemented carbide, (a) The hard coating layer has at least two layers, a lower layer directly contacting the outermost surface of the tool substrate and an upper layer directly contacting the lower layer. The total average layer thickness of the hard coating layer is 0.6 to 21.0 μm, (b) The lower layer is made of a nitride or carbonitride of Ti, and its average layer thickness is 0.05 to 2.0 μm, (c) The upper layer is a composite nitride of Al and Ti. layer or Composite carbonitride layer and the average layer thickness is 0.5 to 20.0 μm; Composition formula: (Al X Ti 1-X )(C Y N 1-Y ), the average content ratio X of Al to the total amount of Ti and Al in the composite nitride layer or the composite carbonitride layer is avg and the composite nitride layer Or the average content ratio Y of C to the total amount of C and N in the composite carbonitride layer avg (However, X avg , Y avg are atomic ratios), respectively, 0.70≦X avg ≦0.90, 0≦Y avg <0.05 and is made of a composite nitride layer or a composite carbonitride layer having a NaCl type face-centered cubic structure, (d) When the residual stress on the cutting edge flank of the tungsten carbide based cemented carbide of the surface-coated tool is S1 and the residual stress on the cutting edge rake face is S2, α)S1 <S2 β)S1≦-200MPa γ) The absolute value of the difference between S1 and S2 is greater than 250 MPa Surface coated cutting tools that meet the requirements. (2) When X-ray diffraction is performed on the upper layer, the ratio of the diffraction intensity value of the cubic (200) plane to the diffraction intensity value of the cubic (111) plane, I(111) / I(200), is 2. The surface-coated cutting tool according to claim 1, wherein the relationship I(111) / I(200) is satisfied. (3) When the residual stress on the cutting edge flank of the tungsten carbide-based cemented carbide of the surface-coated tool is S1 and the residual stress on the cutting edge rake face is S2, α)S1 <S2 β)S1≦-850MPa γ) The absolute value of the difference between S1 and S2 is greater than 500 MPa A surface-coated cutting tool according to (1) or (2), which satisfies the above requirements. It is characterized by the following. In this specification, when a numerical range is indicated using "~" or "-", it means that the lower and upper limits of the numerical range are included. Next, the tool substrate and the hard coating layer of the coated tool of the present invention will be specifically described.

[0012] 1. Tool base; The tool substrate is made of a tungsten carbide-based cemented carbide. In the present invention, the cutting edge flank of the cemented carbide substrate is given a residual stress of -200 MPa or less, more preferably -850 MPa or less, thereby increasing adhesion with the hard coating layer, and the tool can be used as a cutting tool having excellent cutting performance in terms of chipping resistance and wear resistance not only in the continuous high-speed cutting region but also in the intermittent cutting region. Furthermore, by setting the residual stress value on the cutting edge flank of the alloy substrate to -200 MPa or less, more preferably -850 MPa or less, it is possible to suppress the development of cracks during machining and to exhibit high chipping resistance. On the other hand, when the compressive residual stress increases on the rake face as well as on the flank face and the absolute value of the difference between the residual stress value on the flank face and the residual stress value on the rake face falls below 250 MPa, the effect of suppressing the occurrence of thermal cracks is seen, but when plastic deformation occurs in the middle or later stage of processing, the mismatch in the stress states between the coating and the substrate will make peeling of the coating more likely to occur, so the absolute value of the difference between the residual stress value on the flank face and the residual stress value on the rake face needs to be greater than 250 MPa, preferably greater than 500 MPa. The residual stress can be imparted to the tool substrate by wet blasting or dry blasting as a pretreatment before the formation of a hard coating layer described later, or as a posttreatment after the formation of a hard coating layer described later. When wet blasting or dry blasting is performed as a pretreatment prior to the formation of a hard coating layer, the film formation temperature can be set lower than usual to suppress relaxation of residual stress, thereby extending the life of the tool. For example, the application of residual stress to the substrate by blasting is carried out by projecting a dry or wet blasting treatment onto the tool surface using media containing alumina, silicon nitride, or zirconia abrasive grains before or after the formation of a hard coating layer. Blasting conditions; Abrasive grains: ZrO2 grains, Al2O3 grains Grain shape: spherical and / or polygonal Grain size (particle size): 125-425μm (spherical) / <125μm (polygonal) Blasting pressure: 0.1-0.4MPa Blast projected at 70~90° from the flank Projection time: 4-16 seconds

[0013] 2.Hard coating layer; The hardcoat layer comprises a bottom layer and a top layer, and further layers may include a top layer disposed on the top layer. The average thickness of the hard coating layer is set to 0.6 μm or more because adhesion, wear resistance, and chipping resistance cannot be sufficiently ensured over a long period of use if it is less than 0.6 μm. On the other hand, if the average thickness exceeds 21.0 μm, peeling or chipping is likely to occur, so it is preferable to set the average thickness to 21.0 μm or less.

[0014] (a) lower layer; <Average layer thickness> The lower layer is made of Ti nitride or carbonitride and is provided directly on the tool substrate. The average thickness of the lower layer is set to 0.05 μm or more because sufficient adhesion cannot be obtained if the average thickness is less than 0.05 μm. On the other hand, if the average thickness exceeds 2.0 μm, the deformation of the obtained hard coating layer becomes significant and peeling from the tool substrate occurs easily in the early stage of cutting, so the average thickness is set to 2.0 μm or less.

[0015] <Component composition> The composition of the lower layer is not particularly limited as long as it is a nitride or carbonitride of Ti, since it does not impede the object of the present invention. For example, the composition formula is TiC Z N 1-ZWhen expressed as above, the range of 0≦Z≦0.05 is preferable. That is, if Z is contained in an amount greater than 0.05, the hardness of the lower layer increases excessively, and peeling from the interface between the lower layer and the substrate becomes more likely to occur.

[0016] (b) Upper layer <Average layer thickness> The upper layer is made of a composite nitride or composite carbonitride of Ti and Al, and is provided directly on and in contact with the lower layer. If the average thickness of the upper layer is less than 0.5 μm, the hard layer in the entire coating is insufficient and the wear resistance is poor, so the average thickness is set to 0.5 μm or more. On the other hand, if the average thickness exceeds 20.0 μm, the hard layer becomes too thick and peeling or chipping occurs easily during processing, so the average thickness is set to 20.0 μm or less.

[0017] <Component composition> The upper layer is composed of an Al and Ti composite nitride layer (AlTiN layer) or a composite carbonitride layer (AlTiCN layer), and exhibits uniform wear resistance and toughness throughout the entire layer. The Ti component improves high-temperature strength, while the Al component complements high-temperature hardness and heat resistance, so that a low wear coefficient is maintained even under high-temperature cutting conditions, and excellent heat resistance can be demonstrated. The composite nitride or composite carbonitride constituting the Al, Ti composite nitride layer or composite carbonitride layer is specifically represented by the composition formula: (Al X Ti 1-X )(C Y N 1-Y ), but the average Al content X avg If the value of X (atomic ratio) is less than 0.70, the high-temperature hardness is insufficient and the wear resistance decreases. avg When the (atomic ratio) value exceeds 0.90, the relative Ti content decreases, and the (Al X Ti 1-X )(C Y N 1-Y ) The high-temperature strength of the layer itself decreases, making it more susceptible to chipping and fracture. Therefore, the average Al content ratio X avg The value of (atomic ratio) is set to be in the range of 0.70 to 0.90, which is close to the maximum hardness and provides a particularly high effect. In addition, the C component has the effect of improving hardness, but the average content ratio Y avg If the atomic ratio is 0.05 or more, the high-temperature strength decreases, so the average content ratio Y avg (Atomic ratio) is 0≦Y avg It was defined as <0.05.

[0018] <Crystal orientation> The upper layer is made of Al, Ti composite nitride or composite carbonitride (Al X Ti 1-X )(C Y N 1-Y ) can improve the hardness by adopting a NaCl-type face-centered cubic structure (hereinafter sometimes simply referred to as a "cubic structure"). That is, by forming an Al-Ti composite nitride layer or composite carbonitride layer having a high orientation to the (111) plane of a cubic crystal structure, it is possible to increase the hardness. In addition, when the ratio I(111) / I(200) of the diffraction intensity value I(200) of the (111) plane to the diffraction intensity value I(111) of the (200) plane in the upper layer is 1.0 or more, crystal grains are less likely to fall off during processing, so it is desirable to make I(111) / I(200)≧1.0.

[0019] (c)Top layer In the present invention, a top layer can be provided on the AlTi composite nitride layer or the AlTi composite carbonitride layer, which is the upper layer, as necessary, from the viewpoint of improving wear resistance and responding to a wider range of processing applications. Specifically, a layer made of an Al oxide such as α-Al2O3 or κ-Al2O3, or a Ti nitride layer or carbonitride layer can be provided within the range of 4.5 μm or less.

[0020] 3. Method for forming hard coating layer; (a) Method of imparting residual stress to a tool base Residual stress can be imparted to the tool substrate by blasting (wet blasting or dry blasting) as a pretreatment before the formation of the hard coating layer described below, or as a posttreatment after the formation of the hard coating layer. In addition, when the blast treatment is performed as a pretreatment before the formation of a hard coating layer described later, the film formation temperature can be set lower than the conventional treatment temperature to suppress the remaining tensile stress of the hard coating layer, thereby making it possible to extend the life of the cutting tool.

[0021] (b) Method for forming the lower layer The lower layer of the hard coating layer is composed of a compound layer consisting of Ti and nitrogen, or a compound layer consisting of Ti, nitrogen, and carbon. In the first step, a chemical vapor deposition method is used to form a TiN layer or TiCN layer with excellent adhesion by adjusting the reaction gas composition (gas group A) and the reaction atmosphere such as pressure and temperature within appropriate ranges for each compound layer to be formed. [Deposition conditions] 1)TiN layer; Processing method: Deposition using CVD Reactant gas composition (volume %) TiCl4: 3.0~6.0%, N2: 25.0~35.0%, H2: remainder, Reaction atmosphere pressure: 4.0 to 12.0 kPa, Reaction atmosphere temperature: 780~900℃ 2)TiCN layer; Processing method: Deposition using CVD Reactant gas composition (volume %) TiCl4:3.0~6.0%, N2:15.0~30.0%, CH4 or CH3CN: 0.6-2.0%, H2: balance Reaction atmosphere pressure: 7.0 to 12.0 kPa, Reaction atmosphere temperature: 780~900℃

[0022] (c) Method for forming the upper layer <Deposition of the upper layer> Next, in the method for forming the upper layer according to the present invention, the conditions for forming the AlTi composite nitride layer or the AlTi composite carbonitride layer are, for example, to use two types of NH3 gas having different heating temperatures, and the high-temperature ammonia gas can be used to suppress nucleation and promote crystallization, thereby obtaining coarse grains. That is, the method for forming an AlTiN or AlTiCN layer according to the present invention forms a film by alternately repeating the second step (initial nucleus formation step), i.e., the step of forming AlTiN crystals or AlTiCN crystals that serve as initial nuclei for forming an AlTiN or AlTiCN film, and the third step (crystal growth step), i.e., the step of growing the AlTiN crystals or AlTiCN crystals that serve as initial nuclei to form an AlTiN or AlTiCN film. The film formation conditions for each film formation step are outlined below. In particular, in the second step, which is the step of forming the initial nuclei of fine AlTiN or AlTiCN crystals, the following gas group B and gas group C are alternately supplied to the reactor with a phase difference to form a film, and ammonia gas preheated to a high temperature (e.g., 300 to 450°C) is used to promote nucleation. In the subsequent third step, the following gas group D and gas group E are alternately supplied to the reactor with a phase difference to form a film, and the ammonia gas used is changed to ammonia gas preheated to a low temperature (e.g., 50 to 250°C), which suppresses nucleation and promotes crystallization, and allows the desired crystals to be obtained. The number of times the second and third steps are repeated is adjusted according to the target film thickness.

[0023] [Deposition conditions] 1) Second step (initial nucleation step) Processing method: Deposition using CVD method Reactant gas composition (volume %): Gas group B: TiCl4: 0.01-0.04%, AlCl3: 0.01-0.05%, N2: 0~10%, C2H4: 0~0.5%, H2: remaining Gas group C: NH3: 0.1-0.8%, H2: 25.0-35.0%, Reaction atmosphere pressure: 4.0~5.0kPa, Reaction atmosphere temperature: 700~850℃ Supply cycle: 1~5 seconds, Gas supply time per cycle: 0.15 to 0.25 seconds, Phase difference between gas group B supply and gas group C supply: 0.10 to 0.20 seconds Gas group C preheat temperature: 300~450℃

[0024] 2) 3rd process (crystal growth process) Processing method: Deposition using CVD method Reactant gas composition (volume %): Gas group D: TiCl4: 0.01-0.04%, AlCl3: 0.01-0.05%, N2: 0~10%, C2H4: 0~0.5%, H2: remainder, Gas group E: NH3: 0.1-0.8%, H2: 25.0-35.0%, Reaction atmosphere pressure: 4.0~5.0kPa, Reaction atmosphere temperature: 700~850℃ Supply cycle: 1~5 seconds, Gas supply time per cycle: 0.15 to 0.25 seconds, Phase difference between gas group D supply and gas group E supply: 0.10 to 0.20 seconds Preheat temperature for gas group E: 50 to 250°C In addition, the volume percentage of each gas component in the reaction gas composition (volume percentage) in each of the second and third steps indicates the volume percentage of each component calculated with the sum of Gas Group B and Gas Group C being 100 volume % in the second step, and indicates the volume percentage of each component calculated with the sum of Gas Group D and Gas Group E being 100 volume % in the third step. Effect of the Invention

[0025] The surface-coated cutting tool of the present invention imparts a predetermined range of residual stress to each of the flank and rake faces of the tool base, thereby maintaining the wear resistance of the hard coating layer during cutting, enhancing the peeling resistance, suppressing the progression of cracks, and exhibiting resistance to fracture and chipping, thereby improving the tool life. In particular, in milling, thermal cracks that occur from the tool rake face during processing can progress toward the flank side, causing chipping of the cutting edge. Therefore, by keeping the residual stress on the flank face at -200 MPa or less, i.e., under high compressive residual stress, a significant effect in suppressing the progression of cracks can be achieved. On the other hand, when the compressive residual stress increases on the rake face as well as on the flank face, and the absolute value of the difference between the residual stress value on the flank face and the residual stress value on the rake face falls below 250 MPa, the effect of suppressing the occurrence of thermal cracks is seen; however, when plastic deformation occurs in the middle or later stage of processing, the mismatch in the stress states of the coating and the substrate will make peeling of the coating more likely to occur, and therefore it is necessary that the absolute value of the difference between the residual stress value on the rake face and the residual stress value on the flank face be greater than 250 MPa. [Brief description of the drawings]

[0026] [Figure 1] FIG. 1 is a schematic cross-sectional view showing the relationship between a tool substrate of a coated tool according to the present invention and a lower layer (Ti(C)N layer), an upper layer (CVD-AlTiN(C) layer), and a top layer constituting a hard coating layer. [Diagram 2] 1 is a cross-sectional view of an H-shaped can working member which is a workpiece for a coated tool according to the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0027] Next, the coated tool of the present invention will be specifically described with reference to examples. EXAMPLES

[0028] As raw material powders, WC powder, TiC powder, TaC powder, NbC powder, Cr3C2 powder and Co powder, all of which had an average particle size of 1 to 3 μm, were prepared. These raw material powders were mixed to the composition shown in Table 1, wax was added, and the mixture was mixed in a ball mill in acetone for 24 hours. After drying under reduced pressure, the mixture was pressed into a green compact of a predetermined shape at a pressure of 98 MPa. This green compact was vacuum sintered in a vacuum of 5 Pa at a predetermined temperature in the range of 1370 to 1470°C for 1 hour. After sintering, tool substrates A to C made of WC-based cemented carbide and having an insert shape conforming to ISO standard SEEN1203AFTN were produced, respectively.

[0029] Next, each of these tool substrates A to C was placed in a chemical vapor deposition apparatus, and coated tools 1 to 8 of the present invention were produced, respectively, according to the following procedure. As described above, in the present invention, it is assumed that the flanks of the tool substrates A to C are subjected to a blasting treatment as a pretreatment before the formation of a hard coating layer and / or a posttreatment after the formation of a hard coating layer, so that residual stress is imparted to the rake face and the flank of the substrate (see Table 2). Next, in the first step, one of the tool substrates A to C is placed in a chemical vapor deposition apparatus, and film formation is performed for a certain period of time under the temperature and pressure conditions described in the formation conditions (formation symbols) A to H shown in Table 3 using gas group A (TiCl4, N2, CH4, CH3CN, and the remainder H2) having the component composition shown in Table 3.

[0030] For the coated tools 1 to 5 of the present invention, following the first step, in the second step (upper layer initial nucleus formation step), film formation was carried out for a certain period of time based on the gas composition, supply conditions, and gas reaction conditions (pressure, temperature, process time (seconds)) of gas group B and gas group C described in the formation conditions (formation symbols) A to E shown in Table 4, and in the third step (upper layer crystal growth step), film formation was carried out for a certain period of time based on the gas composition, supply conditions, and gas reaction conditions (pressure, temperature, process time (seconds)) of gas group D and gas group E described in the formation conditions (formation symbols) A to E shown in Table 5, to obtain the coated tools 1 to 5 of the present invention shown in Table 7. In addition, for coated tools 6 to 8 of the present invention, following the first step, in the second step (upper layer initial nucleus formation step), a coating was formed under the formation conditions (formation symbols) F to H shown in Table 4, and in the third step (upper layer crystal growth step), a coating was formed under the formation conditions (formation symbols) F to H shown in Table 5. Furthermore, a κ-Al2O3 layer, an l-TiCN layer or an α-Al2O3 layer was formed as the top layer under the formation conditions shown in Table 6, thereby obtaining coated tools 6 to 8 of the present invention shown in Table 7.

[0031] For the purpose of comparison, coatings were formed under the formation conditions a to e shown in Tables 3, 4 and 5 to obtain coated tools 1 to 5 as comparative examples. In addition, after performing coating under the forming conditions f to h shown in Tables 3, 4 and 5, a κ-Al2O3 layer, an l-TiCN layer or an α-Al2O3 layer was formed as the uppermost layer under the forming conditions shown in Table 6, thereby obtaining comparative example tools 6 to 8 shown in Table 8.

[0032] Table 7 shows the residual stresses on the flank and rake faces of the tool substrates of the coated tools 1 to 8 of the present invention, the target average total thickness of the hard coating layer, the target average thickness and type of film formed of the lower layer, the target average thickness of the upper layer, the average Al content (Xavg), the average C content (Yavg), the crystal structure and diffraction line intensity ratio (I(111) / I(200)), and the target average thickness and film formed of the top layer. Table 8 also shows the residual stresses on the flank and rake faces of the tool substrate, the target average total thickness of the hard coating layer, the target average thickness and type of coating of the lower layer, the target average thickness of the upper layer, the average Al content (Xavg), the average C content (Yavg), the crystal structure and diffraction line intensity ratio (I(111) / I(200)), and the target average thickness of the top layer for the comparative coated tools 1 to 8.

[0033] The thickness of the hard coating layer of each of the coated tools 1 to 8 of the present invention and the coated tools 1 to 8 of the comparative examples was measured using a scanning electron microscope (magnification: 5000 times). That is, the tool base was polished so that a cross section perpendicular to the direction was exposed, and each layer was observed at a magnification of 5,000 to 20,000 times. The layer thicknesses were measured at five points within the observed field of view, and the average value was taken as the average layer thickness. The results are shown in Table 7 for coated tools 1 to 8 of the present invention, and in Table 8 for coated tools 1 to 8 of the comparative example. In addition, the average Al content of the upper layer of AlTiN or AlTiCN is X avg (atomic ratio) and the average content ratio Y of C component avg The atomic ratio was determined by irradiating a polished surface of a sample with an electron beam from the surface side of the sample using an electron probe microanalyser (EPMA), and averaging the 10-point analysis results of the characteristic X-rays obtained. The coated tools 1 to 8 of the present invention are shown in Table 7, the coated tools 1 to 8 of the comparative examples are shown in Table 8, and avg and Y avg Indicates the value of.

[0034] The crystal structures of the AlTiN layer and the AlTiCN layer in the upper layers of the hard coating layer of the coated tools of the present invention and the comparative example can be confirmed by performing X-ray diffraction on the surface of the hard coating layer parallel to the tool substrate surface using an X-ray diffractometer with Cu-Kα radiation as the radiation source under conditions of a measurement range (2θ): 20 to 120 degrees, a scan step: 0.013 degrees, and a measurement time per step: 0.48 sec / step, and by observing X-ray diffraction peaks that appear between the diffraction angles of the same crystal planes shown in JCPDS00-038-1420 cubic TiN and JCPDS00-046-1200 cubic AlN (e.g., 36.66 to 38.53°, 43.59 to 44.77°, 61.81 to 65.18°). In addition, from the measured X-ray diffraction peak intensities I(hkl) for the (200) and (111) planes, the ratio of the diffraction peak intensity I(111) for the (111) plane to the diffraction peak intensity I(200) for the (200) plane, I(111) / I(200), can be obtained. The residual stress in the tool base is sin 2The measurements are performed using the Ψ method with an X-ray diffractometer using Cu κα. The measurements are performed using the diffraction peak of the WC(211) plane, with a Young's modulus of 534 GPa and a Poisson's ratio of 0.22.

[0035] [Table 1]

[0036] [Table 2]

[0037] [Table 3]

[0038] [Table 4]

[0039] [Table 5]

[0040] [Table 6]

[0041] [Table 7]

[0042] [Table 8]

[0043] Next, with each of the various coated tools clamped to the tip of a tool steel cutter using a fixing jig, face milling of welded members was carried out for the coated tools 1 to 8 of the present invention and the comparative coated tools 1 to 8, as shown below, and the maximum machining length until tool chipping was evaluated. The results are shown in Table 9.

[0044] ≪Cutting conditions≫ Cutting test: Wet face milling continuous processing Work material: SS400 welded material T1=30mm, width 100mm, length 400mm H-shaped can manufacturing part diagram 2 Rotation speed: 637 min -1 , Cutting speed: 250m / min. Cutting depth: 3.0mm, Feed per tooth: 0.2mm / tooth Cutting time: Cutting tip is damaged or cutting length is 8m and processing is stopped

[0045] [Table 9]

[0046] As is clear from the cutting test results shown in Table 9, the coated tool of the present invention controls the residual compressive stress on the flank and rake faces of the tungsten carbide-based cemented carbide substrate to arbitrary values, and the hard coating layer directly in contact with the surface of the tool substrate comprises a lower layer of a Ti nitride or carbonitride layer and an upper layer of a composite nitride layer or composite carbonitride layer of Al and Ti having a NaCl-type face-centered cubic crystal structure, thereby preventing chipping and other problems caused by the falling off of fine crystal grains and exhibiting excellent fracture resistance and wear resistance over a long period of time. [Industrial Applicability]

[0047] As described above, the surface-coated cutting tool of the present invention exhibits excellent wear resistance, fracture resistance and chipping resistance when used in continuous cutting and intermittent cutting of ordinary steels, particularly when used in intermittent cutting of stainless steels and hard-to-cut materials where a fused surface remains, or in rough cutting which requires a large depth of cut with an emphasis on machining efficiency, and therefore fully satisfies the needs for high performance cutting equipment, labor-saving and energy-saving cutting, and cost reduction.

Claims

1. A surface-coated cutting tool having a hard coating layer on a surface of a tool substrate made of a tungsten carbide-based cemented carbide, (a) the hard coating layer has at least two layers, namely a lower layer directly contacting the outermost surface of the tool substrate and an upper layer directly contacting the lower layer, and the total average thickness of the hard coating layer is 0.6 to 21.0 μm; (b) the lower layer is made of a Ti nitride or carbonitride and has an average layer thickness of 0.05 to 2.0 μm; (c) the upper layer is a composite nitride layer or a composite carbonitride layer of Al and Ti, and the average layer thickness is 0.5 to 20.0 μm; Composition formula: (Al X Ti 1-X ) (C Y N 1-Y ) the average content ratio X of Al to the total amount of Ti and Al in the composite nitride layer or the composite carbonitride layer avg and an average content ratio Y of C to the total amount of C and N in the composite nitride layer or the composite carbonitride layer. avg (However, X avg , Y avg are atomic ratios), and 0.70≦X avg ≦0.90, 0≦Y avg <0.05 and is made of a composite nitride layer or a composite carbonitride layer having a NaCl type face-centered cubic structure, (d) When the residual stress on the flank of the cutting edge of the tungsten carbide based cemented carbide of the surface-coated tool is S1 and the residual stress on the rake face of the cutting edge is S2, α) S1<S2 β) S1≦-200MPa γ) The absolute value of the difference between S1 and S2 is greater than 250 MPa A surface-coated cutting tool characterized by satisfying each of the above requirements.

2. When X-ray diffraction was performed on the upper layer, the ratio of the diffraction intensity value of the cubic (111) plane to the diffraction intensity value of the cubic (200) plane, I(111) / I(200), was:

2. The surface-coated cutting tool according to claim 1, wherein the relationship: 1.0≦I(111) / I(200) is satisfied.

3. When the residual stress on the flank of the cutting edge of the tungsten carbide based cemented carbide of the surface-coated tool is S1 and the residual stress on the rake face of the cutting edge is S2, α) S1<S2 β) S1≦-850MPa γ) The absolute value of the difference between S1 and S2 is greater than 500 MPa 3. The surface-coated cutting tool according to claim 1 or 2, which satisfies the above requirements.

Citation Information

Patent Citations

  • Surface-coated tungsten carbide base cemented carbide cutting tool excellent in wear-resistance and breakage-resistance

    JP1994055311A

  • Edge replaceable cutting tip and method of manufacturing the same

    JP2011189505A

  • Surface-coated cutting tool and method of manufacturing the same

    JP2017124463A

  • Tools with tialn coating

    JP2018522748A

  • Surface-coated cutting tool excellent in defect resistance

    JP2020157457A